Vision-Based Real-Time Indoor Positioning System for Multiple Vehicles. Issue 2 (2020) - Kloock, Maximilian; Scheffe, Patrick; Tülleners, Isabelle; Maczijewski, Janis; Kowalewski, Stefan; Alrifaee, Bassam
Abstract: We propose a novel external indoor positioning system that computes the position and orientation of multiple model-scale vehicles. For this purpose, we use a camera mounted at a height of 3.3 m and LEDs attached to each vehicle. We reach an accuracy of about 1.1 cm for the position and around 0.6° for the orientation in the mean. Our system is real-time capable with a soft deadline of 20 ms. Moreover, it is robust against changing lighting conditions and reflections.